Multivisceral organ failure related to leptospirosis in pregnant patient - Hicham, Sbai (Medknow Publications & Media Pvt Ltd, 2013)
Leptospirosis is the most widespread zoonosis in the world. It is caused by pathogenic leptospira infection. This infection is also an uncommon cause of hepatorenal failure. Indeed, hemolysis, elevated liver enzyme levels and low platelet count syndrome, and acute fatty liver of pregnancy are specific to the pregnant state. Leptospirosis is rarely described in pregnancy; it might mimic puerperal sepsis or hepatorenal failure associated with pregnancy induced hypertension. We report a case of leptospirosis presenting as multiple organ failure during third trimester of pregnancy with a good outcome.